Diagnostic Accuracy of the Inferior Vena Cava Collapsibility to Predict Fluid Responsiveness in Spontaneously Breathing Patients With Sepsis and Acute Circulatory Failure. Issue 3 (March 2017) - Preau, Sebastien; Bortolotti, Perrine; Colling, Delphine; Dewavrin, Florent; Colas, Vincent; Voisin, Benoit; Onimus, Thierry; Drumez, Elodie; Durocher, Alain; Redheuil, Alban; Saulnier, Fabienne
Abstract : Objective: To investigate whether the collapsibility index of the inferior vena cava recorded during a deep standardized inspiration predicts fluid responsiveness in nonintubated patients. Design: Prospective, nonrandomized study. Setting: ICUs at a general and a university hospital. Patients: Nonintubated patients without mechanical ventilation ( n = 90) presenting with sepsis-induced acute circulatory failure and considered for volume expansion. Interventions: We assessed hemodynamic status at baseline and after a volume expansion induced by a 30-minute infusion of 500-mL gelatin 4%. Measurements and Main Results: We measured stroke volume index and collapsibility index of the inferior vena cava under a deep standardized inspiration using transthoracic echocardiography. Vena cava pertinent diameters were measured 15–20 mm caudal to the hepatic vein junction and recorded by bidimensional imaging on a subcostal long-axis view. Standardized respiratory cycles consisted of a deep standardized inspiration followed by passive exhalation. The collapsibility index expressed in percentage equaled the ratio of the difference between end-expiratory and minimum-inspiratory diameter over the end-expiratory diameter. After volume expansion, a relevant (≥ 10%) stroke volume index increase was recorded in 56% patients. In receiver operating characteristic analysis, the area under curve for that collapsibility index was 0.89 (95% CI, 0.82–0.97). When such index is superior or equal to 48%, fluid responsiveness is predicted with a sensitivity of 84% and a specificity of 90%. Conclusions: The collapsibility index of the inferior vena cava during a deep standardized inspiration is a simple, noninvasive bedside predictor of fluid responsiveness in nonintubated patients with sepsis-related acute circulatory failure. Abstract : Supplemental Digital Content is available in the text.